2007
DOI: 10.1364/ol.32.002291
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront reconstruction of an optical vortex by a Hartmann-Shack sensor

Abstract: Reconstruction the phase front of a vortex laser beam is conducted by use of a Hartmann-Shack wavefront sensor. The vortex beam in the form of the Laguerre-Gaussian LG(0)(1) mode is generated with the help of a spiral phase plate. The new reconstruction technique based on measured wavefront gradients allows one to restore the singular phase surface with good accuracy, whereas the conventional least-squares approach fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 14 publications
0
28
0
2
Order By: Relevance
“…More details are presented in Supplementary Section S5. As a final proof we measured the wavefront of the XUV beam 21 with a Hartmann sensor. Similar experiments in the optical range have shown that the wavefront should wind up like a screw around the singularity in the centre 22 .…”
mentioning
confidence: 99%
“…More details are presented in Supplementary Section S5. As a final proof we measured the wavefront of the XUV beam 21 with a Hartmann sensor. Similar experiments in the optical range have shown that the wavefront should wind up like a screw around the singularity in the centre 22 .…”
mentioning
confidence: 99%
“…Previous studies used a closed path associated with 2 × 2-neighboring measurement points. [16][17][18][19][20][21][22] Instead, here we propose an alternate closed path that connects the centers of the eight nearest neighbors of measurement points, which we call an eight-connected contour in the rest of this paper (Fig. 1).…”
Section: Eight-connected Closed Contour For Optical Vortex Detectionmentioning
confidence: 99%
“…2,16 The presence and absence of phase singularities in a light beam can be determined according to the nonzero (local peak) values of the contour summations. Some improvements and modifications have been made to reduce noise; [17][18][19] however, the spatial resolution of measurements with the SH-WFS is limited by the lens size of the lenslet array.…”
Section: Introductionmentioning
confidence: 99%
“…Как было указано выше, матрица W является ком-плексной, поэтому должны быть точно определены не только амплитуды её элементов |w µν |, но и межмодовые фазы φ µν . Для получения всей информации о коэффици-ентах w µν может быть использован известный подход, основанный на сенсоре Шака-Хартманна [26,27]. При-нятая информация о форме фронта позволяет декомпо-зировать моды, используя выражение (9).…”
Section: физическая модель Mdm-каналаunclassified